E-Service Quality, Promotion and Price Perception on Loyalty of Traveloka Users - Anissa Putri; Feby Kinanda; Oktavia Marpaung; Binton Siburian (International Journal of Informatics, Economics, Management and Science (IJIEMS), 2022)
This research was conducted to determine the effect of each variable, e-service quality, promotion, and price perception on loyalty users. The type of research used is quantitative analysis, the data collectiontechnique used is multiple linear regression analysis. Furthermore, the samplingtechnique used is random sampling with a total of 105 respondents. The results showed that from the third factor, price perception had apositive and significant effect, while the quality of e-service and promotion had a positive and insignificant effectIt is hoped that Traveloka will continue to strive to improve the quality of e-service quality, promotions and price perception to help increase loyalty, so that more and more people use the Traveloka application in Jakarta..